Screening of Potential Free Radicals Scavenger and Antibacterial Activities of Purwoceng (Pimpinella alpina Molk) - Retno Wahyuningrum,; Pri Iswati Utami,; Binar Asrining Dhiani,; Malikhah Kumalasari ,; Rizka Sari Kusumawardani, (Tropical Life Sciences Research, 2016)
Purwoceng (Pimpinella alpina Molk) is a traditional medicinal plant used for its aphrodisiac values. This plant was originated Dieng Plateu, Central Java, Indonesia. Purwoceng has been reported to contain steroid, flavonoids, glycoside, saponins, tannins, and phenolic. Based on secondary metabolite compounds of Purwoceng herbs, a research need to be done to determine the other potential free radicals scavenger and antibacterial activities of Purwoceng. The objectives of this research are to screen the potential free radicals scavenger activity of in vitro using DPPH (1,1 diphenyl-2-picryl-hydrazil) radicals and NO• (nitric oxide) radicals, and antibacterial activity of Purwoceng. The extraction is done by a maceration method with petroleum ether, ethyl acetate, and ethanol solvent, respectively. Free radicals scavenger test was performed using DPPH radicals and NO• radicals, while antibacterial activity screening was performed using agar diffusion test. The results showed that ethyl acetate extract of Purwoceng has free radical scavenger activity with IC50 53.07 ppm lower than butylated hydroxytoluene. Ethyl acetate extract and ethanol extract of Purwoceng have antibacterial activity against Staphyloccus aureus, Escherichia coli, and MG42 bacterial isolate.